Enhanced electrochromic and energy storage performance in mesoporous WO3 film and its application in a bi-functional smart window - Wang, Wei-Qi; Wang, Xiu-Li; Xia, Xin-Hui; Yao, Zhu-Jun; Zhong, Yu; Tu, Jiang-Ping (Nanoscale, 2018)
Construction of multifunctional photoelectrochemical energy devices is of great importance to energy saving. In this study, we have successfully prepared a mesoporous WO3 film on FTO glass via a facile dip-coating sol-gel method; the designed mesoporous WO3 film exhibited advantages including high transparency, good adhesion and high porosity. Also, multifunctional integrated energy storage and optical modulation ability are simultaneously achieved by the mesoporous WO3 film. Impressively, the mesoporous WO3 film exhibits a noticeable electrochromic energy storage performance with a large optical modulation up to 75.6% at 633 nm, accompanied by energy storage with a specific capacity of 75.3 mA h g-1. Furthermore, a full electrochromic energy storage window assembled with the mesoporous WO3 anode and PANI nanoparticle cathode is demonstrated with large optical modulation and good long-term stability. Our research provides a new route to realize the coincident utilization of optical-electrochemical energy.Construction of multifunctional photoelectrochemical energy devices is of great importance to energy saving. In this study, we have successfully prepared a mesoporous WO3 film on FTO glass via a facile dip-coating sol-gel method; the designed mesoporous WO3 film exhibited advantages including high transparency, good adhesion and high porosity. Also, multifunctional integrated energy storage and optical modulation ability are simultaneously achieved by the mesoporous WO3 film. Impressively, the mesoporous WO3 film exhibits a noticeable electrochromic energy storage performance with a large optical modulation up to 75.6% at 633 nm, accompanied by energy storage with a specific capacity of 75.3 mA h g-1. Furthermore, a full electrochromic energy storage window assembled with the mesoporous WO3 anode and PANI nanoparticle cathode is demonstrated with large optical modulation and good long-term stability. Our research provides a new route to realize the coincident utilization of optical-electrochemical energy.